Modification of boron-doped diamond with gold-palladium nanoparticles for CO2 electroreduction. Issue 1 (February 2020) - Kumik, A; Ivandini, T A; Wibowo, R
Abstract: Modification of boron-doped diamond (BDD) with gold-palladium nanoparticles (AuPdNPs) was performed for an application in electrochemical reduction of CO2 . Preparation of the colloidal AuPdNPs involved two steps, including the synthesis of gold nanoparticles (AuNPs) and the growth of palladium on the surface of AuNPs. BDD, which had been terminated with allylamine under UV light irradiation for6 h, then, was immersed in the colloidal AuPdNPs. Characterization of the nanoparticles by using Tunneling Electron Microscopy (TEM) showed flowers-like nanoparticles with an average size of 40 nm, while characterization of the modified BDD showed the Au and Pd surface coverage of 4.4 % and 6.0 %, respectively, on BDD surface. The electrochemical reduction of CO2 at the modified BDD was performed in a two-compartments cell with 0.1 M NaCl solution in the cathode chamber and 0.1 M Na2 SO4 solution in the anode chamber. By applying the potential -0.9 V (vs. Ag/AgCl) in the system for 60 min, it showed the faradaic efficiency of the system at approximately 84.65 % with acetic acid as one of the products.